2018
DOI: 10.1080/16506073.2018.1508247
|View full text |Cite
|
Sign up to set email alerts
|

Look before you leap: the role of negative urgency in appraisals of ambiguous and unambiguous scenarios in individuals high in generalized anxiety disorder symptoms

Abstract: Negative interpretation bias, the propensity to make threatening interpretations of ambiguous information, is associated with symptoms of generalized anxiety disorder (GAD). Apart from its relationship with intolerance of uncertainty (IU), little is known about what explains the presence of this cognitive bias in GAD. One factor may be negative urgency (NU), the tendency to take rash action when distressed, which is related to GAD symptoms and to cognitive biases in nonclinical populations. The aim of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
3
4
0
Order By: Relevance
“…Higher levels of intolerance of uncertainty were associated with higher levels of overall interpretation bias and negative interpretation bias. This finding is consistent with previous research and suggests that individuals who are intolerant of uncertainty are more likely to interpret ambiguous social information as negative or threatening (Anderson et al, 2012;Malivoire et al, 2019;Oglesby et al, 2019). Moreover, this study is the first, to our knowledge, to demonstrate an association between intolerance of uncertainty and positive interpretation bias, such that lower levels of intolerance of uncertainty were associated with higher levels of positive interpretation bias.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Higher levels of intolerance of uncertainty were associated with higher levels of overall interpretation bias and negative interpretation bias. This finding is consistent with previous research and suggests that individuals who are intolerant of uncertainty are more likely to interpret ambiguous social information as negative or threatening (Anderson et al, 2012;Malivoire et al, 2019;Oglesby et al, 2019). Moreover, this study is the first, to our knowledge, to demonstrate an association between intolerance of uncertainty and positive interpretation bias, such that lower levels of intolerance of uncertainty were associated with higher levels of positive interpretation bias.…”
Section: Discussionsupporting
confidence: 92%
“…Intolerance of uncertainty and attentional control have been identified as key cognitive risk factors related to both social anxiety and interpretation bias (Boelen & Reijntjes, 2009; Oglesby et al, 2019; Raines et al, 2019). Individuals who are intolerant of uncertainty tend to react negatively to uncertain situations and are more likely to interpret ambiguous information as threatening (Anderson et al, 2012; Malivoire et al, 2019; Oglesby et al, 2019). Similarly, impairments in attentional control have been associated with elevated levels of social anxiety and negative interpretation bias, as these individuals may have difficulty inhibiting threatening interpretations of ambiguity and disengaging from threat-related information to shift their attention to more benign alternatives (Derakshan & Eysenck, 2009; Muris et al, 2007; Raines et al, 2019).…”
mentioning
confidence: 99%
“…Specifically, individuals with elevated levels of NU were found to rate ambiguous scenarios as more hostile after controlling for emotionality and trait aggression. This idea is in keeping with recent findings by Malivoire and colleagues in the context of GAD, which suggest that NU may contribute to the development of more hostile interpretations (Malivoire et al, 2019). In particular, Malivoire et al (2019) found that elevated NU levels were predictive of more negative evaluations of ambiguous security-related scenarios in individuals reporting chronic anxiety.…”
Section: A More Complex Pathway To Aggression Involving Negative Urge...supporting
confidence: 86%
“…Uncertainty is inherently anxiety-provoking, as it indicates that we cannot actively seek potential rewards or avoid losses or threats 172 . Intolerance of uncertainty is a core symptom of many psychiatric disorders, including depression 186 , anxiety 187 , eating disorders 188 and autism 189 . People with higher intolerance of uncertainty may overestimate the likelihood or severity of negative outcomes 190 , worry about the future in an effort to reduce uncertainty 191 and avoid risk 172 .…”
Section: Box 3 | the Pulvinar And Intolerance Of Uncertaintymentioning
confidence: 99%